Strategi Kepemimpinan Kepala Madrasah dalam Meningkatkan Profesionalisme Guru di Madrasah Aliyah Hidayatul Mubtadiin Lampung Selatan - Titi Suryani; Nurul Hidayati Murtafiah; Nur Widiastuti (Departement of Mathematics Education, 2023)
The main objectives of this study are: 1) To find out the Madrasah Principal's Leadership Strategy in Increasing Teacher Professionalism at Madrasah Aliyah Hidayatul Mubtadiin 2) To find out the supporting and inhibiting factors in Improving Teacher Professionalism at Madrasah Aliyah Hidayatul Mubtadiin. This research method uses a qualitative approach, the method used in this research is using, Observation, Interview, Documentation. The results showed that the leadership strategy of the madrasa head in increasing teacher professionalism at Madrasah Aliyah Hidayatul Mubtadiin, namely: creating conducive situations and conditions in the work environment, increasing discipline for all educators, carrying out strict selection of teaching staff, providing welfare guarantees for, Evaluate each activity that has been implemented. Supporting factors namely; apply the principles of respect for educators who have work creativity and innovation, have sufficient budget for madrasah development, have adequate and supporting facilities and infrastructure, educators have high work enthusiasm and innovation in carrying out their duties. Inhibiting factors are: there are still many educators who have not been able to properly utilize the facilities and infrastructure owned by madrasas as media in learning, there are still some